Spectrum of renal cortical necrosis in acute renal failure in eastern India. Issue 834 (April 1995) - Prakash, J.; Tripathi, K.; Pandey, L. K.; Sahai, S.; Usha; Srivastava, P. K.
Abstract : Renal cortical necrosis is an uncommon cause of acute renal failure. We report 23 cases of biopsy-proven renal cortical necrosis which constituted 6.3% (23/363) of all cases of acute renal failure studied over a period of seven years (1985-92). The patients were divided into two groups: obstetric and non-obstetric. Obstetric complications were responsible for renal cortical necrosis in 15 (65.2%) patients while non-obstetric conditions accounted for the remaining eight (34.8%) cases. The overall incidence of cortical necrosis in obstetric acute renal failure was 15/63 (23.8%) patients, the incidence being nearly equal in early (20.5%) and late (29%) pregnancy. Post-abortum renal failure was the sole cause of cortical necrosis in early pregnancy in the obstetric group. Haemolytic uraemic syndrome (three patients) and septicaemia (two patients) were the main cause of necrosis in the non-obstetric group. The cortical necrosis was diffuse and patchy in 17 and six patients, respectively. The disease had a fatal prognosis in 20 (87%) patients; mortality was due to uraemic complications and infections in the majority of patients. The high frequency of post-abortum renal cortical necrosis in our patients is similar to the experience of other Indian workers.